Assessment of Apixaban Prescribing Patterns for Nonvalvular Atrial Fibrillation in Hospitalized Patients. Issue 1 (January 2018) - Gibson, Caitlin M.; Smith, Carmen B.; Davis, Sondra; Scalese, Michael J.
Background: Apixaban is a direct oral anticoagulant (DOAC) for the prevention of stroke and systemic embolism in patients with nonvalvular atrial fibrillation (NVAF). Other DOACs require renal dose adjustments based solely on creatinine clearance. Apixaban differs in that its dose adjustments are more complex, potentially leading to prescribing errors.Objective: To determine if adherence to Food and Drug Administration (FDA)-approved dosing for apixaban is maintained in hospitalized patients with NVAF.Methods: Patients ≥18 years old with NVAF who received apixaban during admission to 1 of 3 hospitals were evaluated. The primary outcome was to determine if providers order apixaban in accordance with FDA-approved dosages. Secondary outcomes included determining if pharmacist review increased the number of orders in accordance with FDA-approved dosing, which of the 3 criteria (age ≥80 years, body weight ≤60 kg, or serum creatinine ≥1.5 mg/dL) were met in patients receiving off-label dosing, and the rationale for off-label prescribing.Results: A total of 556 patients met inclusion criteria. Apixaban was dosed according to FDA labeling by providers in 83.4% (n = 464) of orders. After pharmacist review, 87.0% (n = 484) of orders were at the approved dose, 12.2% (n = 68) were underdosed, and 0.7% (n = 4) were overdosed. Most patients who were underdosed met only 1 dose reduction criterion—most commonly age ≥80 years (56.0%). Reasons for off-label dosing included home dose continuation (39.0%), history of or perceived bleeding risk (30.5%), or unspecified/other (30.5%).Conclusions: The majority of apixaban orders for NVAF were based on FDA-approved dosages after provider entry and pharmacist review.